A realistic perspective for CO2 triggered tuning of electrical conductivity. Issue 48 (28th October 2022) - Sha, Mizaj Shabil; Kumar, Bijandra; Abdullah, Aboubakr M.; Muthusamy, Suresh; Kumar Sadasivuni, Kishor
Abstract : Schematic of tuning of electrical conductivity of zinc coupled with carbon capture and utilisation strategy. Abstract : To seek sustainable CO2 sequestration and conversion, an electrochemical cell has been investigated for carbon capture and utilization strategy (CCU). In this cell, atmospheric CO2 is captured under ambient conditions and incorporated into power generation using zinc nanopowder as the catalyst. As a result, a method was developed to tune the electronic property of zinc by passing CO2 . It was observed that nearly three orders of magnitude of conductivity could be changed along with achieving a carbon capture strategy. The system also exhibited good stability. In this process, it was observed that efficient current generation could be achieved due to zinc's active participation as a catalyst. The detailed physicochemical characterizations of catalysts were also examined. XRD, FTIR and TEM analysis perform the structural and morphological characterization. The system performance was further investigated using different criteria.